Novel immunobiologics for psoriasis - Ghosh N.; Singh P.N.; Kumar V. (My University, 2025)
Psoriasis is one of the most common human skin diseases and is considered to have key genetic contributions. It is characterized by excessive growth and aberrant differentiation of keratinocytes, but is reversible with appropriate therapy with the possibilities of recurrence. The trigger of the keratinocyte response is thought to be the activation of the cellular immune system with T cells, dendritic cells and various immune related cytokines and chemokines being implicated in pathogenesis. Immunosuppressants like cyclosporine and methotrexate were used earlier in the treatment of psoriasis, however their use was associated with severe adverse effects due to down regulation of immune system. The most recent advances in therapies for psoriasis target specific immune components of psoriasis and promise to have high therapeutic efficacy with low adverse effects. This review focuses on the novel therapies aimed to specifically modulate the dysregulated immune system with minimal adverse effects.